PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN TAMU DI CIWIDEY VALLEY RESORT - Agastya, Muhamad Zaidan; Arif, Dally Nur; Putri, Dias Pratami (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2024)
The purpose of this study is to analyze and determine the influence of service quality whose dimensions consist of reliability, responsiveness, assurance, empathy, and tangible on guest satisfaction at Ciwidey Valley Resort partially and simultaneously. The research method used in this study is quantitative. The population in this study is guests who have stayed at Ciwidey Valley Resort. The sample obtained using the slovin formula amounted to 100 respondents. Data was collected through a questionnaire distributed to guests who had stayed at Ciwidey Valley Resort. The data analysis used in this study is multiple linear regression analysis with the IBM SPSS 27 tool. The results of this study are interpreted that the quality of service does not have a partial influence and has a simultaneous influence on guest satisfaction at Ciwidey Valley Resort. It can be concluded that if the quality of service provided at Ciwidey Valley Resort is good, it tends to provide a satisfactory experience for guests who have stayed, which is measured by the level of satisfaction with the service received.